Korelasi Antara KBM Agama Islam dengan Hasil Belajar Agama Islam Siswa SMAN X Surabaya - mukhtar Uddin (Analisa: Journal of Social Science and Religion, 2009)
Growth of technology at the moment very fast. The fast growth can affect negativeand positive to the rising generation. One of effort able to prevent negative impact toeducation of religion. August values of religion expected can overcome negative impactof growth of technology. Student participant in SMA is some of the rising generationsobtaining education of religion in school. This research express KBM PAI berkolerasisejauhmana with result learn student Islam. such variable is storey;level often itemsscope Iesson of Islam with variable and Islam mount according to result evaluate onthe chance of student.Keyword: Correlation, School activity, Result of Learning.